ZAHIR BEYBARS IS A GREAT COMMANDER - Aripova Zukhra (Journals Park Publishing, 2023)
This scientific article investigates and analyzes the processes of formation of the sovereignty of the Mamluks who dominated Egypt in 1250-1517, the events that led to the arrival of the Egyptians to Egypt, the reign of Sultan Zahir Beibars and his relationship with the Abbasid caliphs were studied and analyzed.
Keywords: Egypt, country, sultan, bourgeois, bourgeois, history, caliphate, madrassa, building, city, historical process, science.